PENENTUAN WAKTU SALAT ZUHUR DENGAN BATAS AWAL ZAWAL AL-SYAMS - Badrun Taman; Fafa Redy (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2019)
There are two different consepts of zawal al-syams. First consept shows that zawal al-syams is sun position when it’s east disk get through meridian. Second consept talk that the zawal al-syams is sun position which it’s center point accros meridian. This different implicate that doing zuhur prayer when sun is in istiwa’ position is legitimated according to second consept, and isn’t legitimated  in the view of first consept, because it doesn’t enter initial limit of zawal al-syams yet. This description bring up two problems, there are: how is the zawal al-syams consept according to Islamic jurisprudence of prayer time, and how is the initial limit of zawal al-syams in the view of Islamic prayer time jurisprudence. This is qualitative-library research with descriptif-analitical-comparative method and normative-astronomic approach. The research conclusions are zawal al-syams in Islamic jurisprudence perspective is zawal zhahiri (observable zawal) with zhuhur fai’ al-zawal criteria means appearance of zawal shadow. So that, Zawal zhahiri is slipping of the sun from meridian signed bay appearance of shadow increase ini length moving to the east. Initial limit of zawal is started from the first motion of sun.